2012
DOI: 10.1016/j.jvs.2012.06.081
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of remote endarterectomy versus endovascular intervention for TransAtlantic Inter-Society Consensus II D femoropopliteal lesions

Abstract: RE is a safe, effective, and durable procedure for TASC-II D lesions. Our data demonstrate a significantly higher primary, assisted primary, and secondary patency of RE vs ENDO procedures. Furthermore, overall secondary patency rates remain within the standard limits, although preoperative CLI and dyslipidemia continue to be associated with worse outcomes. Taken together, these data suggest that RE should be considered better than an endovascular procedure in SFA long-segment occlusion treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 33 publications
1
31
1
2
Order By: Relevance
“…Möglicherweise haben PTFE-gecoverte Stentgrafts eine bessere Prognose (271). Eine RCT bei Patienten mit CLI und femoropoplitealen TASC B-und C-Läsionen wurde allerdings vorzeitig beendet, da die Offenheit von Bypasses nach 1 Jahr mit 95 % signifikant höher war als die von PTFE-Stentgrafts (46 %) (396).…”
Section: Gefäßchirurgie Der Beckenarterienunclassified
“…Möglicherweise haben PTFE-gecoverte Stentgrafts eine bessere Prognose (271). Eine RCT bei Patienten mit CLI und femoropoplitealen TASC B-und C-Läsionen wurde allerdings vorzeitig beendet, da die Offenheit von Bypasses nach 1 Jahr mit 95 % signifikant höher war als die von PTFE-Stentgrafts (46 %) (396).…”
Section: Gefäßchirurgie Der Beckenarterienunclassified
“…Previous studies reported no significant difference in complications rates between the subintimal and intraluminal groups. 12, 16 As the major complication rates of subintimal angioplasty in the previous studies varied from 0% to 13%, 7,12,15,16 the periprocedural complication rates (4.1% for major complicates and 9.1% for all complications) observed in this study appear to be still rather low.…”
Section: Mid-term Outcomesmentioning
confidence: 49%
“…After RSFAE primary, assisted primary, and secondary patencies are evidently higher than after an endovascular treatment. 11 If the saphenous vein is not usable, RSFAE should be regarded as a better choice, because it is mini-invasive and prosthetic graft material cannot be necessarily used. 12…”
Section: Resultsmentioning
confidence: 99%